(untitled) (Research, Society and Development, 2021)
Systemic intoxication of local anesthetics (LAs) is one of the most feared complications in anesthesia due to the risk for the cardiovascular system, for the central nervous system and, in particular, for triggering cardiorespiratory arrest, even in healthy patients. ALs interrupt nerve conduction, interfering with the function of all organs in which the conduction or transmission of nerve impulses occurs. One of the main factors involved is the rapid increase in plasma concentration. ALs in the constrictor vessels reduce poisoning by their slow absorption of anesthetic salt. In addition to providing anesthesia and/or analgesia for the patient, the dentist performing the procedure must always keep in mind that the prevention of these complications must always be observed. The aim of this article was to carry out a bibliographical survey on intoxication by local anesthetics, trying to emphasize the main symptoms, treatment and prevention. Bibliographic searches were performed in the SciELO, MEDLINE and PubMed databases, with articles published between 2010 and 2021.